Diversity and Green Synthesis of Various Metal Nanoparticles (MNPs) - Makwana, Dhara B.; Mevada, Adwait (The Scientific Temper, 2025)
The review provides a comprehensive overview of metal nanoparticles (MNPs) synthesized using green methods, including gold, silver, copper, zinc oxide, and other metallic nanoparticles. The synthesis of MNPs has become a cornerstone of nanotechnology, given their unique physicochemical properties and vast applications. Traditional methods for MNP synthesis often involve hazardous chemicals and energy-intensive processes, raising environmental and safety concerns. In response, green synthesis has emerged as a sustainable and eco-friendly alternative. This review explores the diversity of green synthesis approaches for producing MNPs, emphasizing their advantages, challenges, and potential applications. The article highlights the role of biomolecules, in mediating the reduction of metal ions and stabilizing nanoparticles. This article underscores the transformative potential of green synthesis in advancing the sustainable production of MNPs while minimizing ecological impact.